Hemiarthroplasty vs. internal fixation for nondisplaced femoral neck fracture in mainland China: a cost-effectiveness analysis - Wang, Shengchun; Tan, Lingjie; Sheng, Bin (Frontiers in Surgery, 2024)
ObjectiveNondisplaced femoral neck fractures constitute a substantial portion of these injuries. The optimal treatment strategy between internal fixation (IF) and hemiarthroplasty (HA) remains debated, particularly concerning cost-effectiveness.MethodsWe conducted a cost-effectiveness analysis using a Markov decision model to compare HA and IF in treating nondisplaced femoral neck fractures in elderly patients in China. The analysis was performed from a payer perspective with a 5-year time horizon. Costs were measured in 2020 USD, and effectiveness was measured in quality-adjusted life-years (QALYs). Sensitivity analyses, including one-way and probabilistic analyses, were conducted to assess the robustness of the results. The willingness-to-pay threshold for incremental cost-effectiveness ratio (ICER) was set at $11,083/QALY following the Chinese gross domestic product in 2020.ResultsHA demonstrated higher cumulative QALYs (2.94) compared to IF (2.75) but at a higher total cost ($13,324 vs. $12,167), resulting in an ICER of $6,128.52/QALY. The one-way sensitivity analysis identified the costs of HA and IF as the most influential factors. Probabilistic sensitivity analysis indicated that HA was more effective in 69.3% of simulations, with an ICER below the willingness-to-pay threshold of $11,083 in 58.8% of simulations.ConclusionsHA is a cost-effective alternative to IF for treating nondisplaced femoral neck fractures in elderly patients in mainland China.